Tamoxifen-induced severe hot flashes and endoxifen levels: is dose reduction a safe and effective strategy?. (August 2019) - Lee, Clara I.; Fox, Peter; Balakrishnar, Bavanthi; Balleine, Rosemary L.; Gao, Bo; Provan, Pamela; Coulter, Sally; Liddle, Christopher; Hui, Rina; Wong, Mark; Gurney, Howard; Wilcken, Nicholas
Abstract: Objectives: Severe hot flash (HF) toxicity due to tamoxifen can compromise compliance. We previously found that HFs did not correlate with endoxifen level or CYP2D6 genotype. In this study, we reduced tamoxifen dose in patients with severe HFs to determine whether HFs were ameliorated whilst maintaining a purported therapeutic endoxifen level of >15 nM. Materials and methods: Twenty patients with severe HFs on 20 mg TAM had CYP2D6 genotype, trough level tamoxifen and metabolites measured with Loprinzi HF scores (HFS) derived before and after DR of tamoxifen to 10 mg. Other data collected included demographics, smoking, alcohol, menstrual and breast cancer history, previous chemotherapies, concurrent medications, BMI and other tamoxifen toxicities. Results: At the 20 mg tamoxifen dose, endoxifen levels were 25.6, 0–91.9 nM (median, range) with HFS 131, 22–1482 (median, range). Upon DR to 10 mg, median endoxifen level fell to 14.1, 0.6–71.9 nM (difference in means p = 0.11, two-tailed T test) with HFS 47, 5–864 (difference in means p = 0.24, two-tailed T test). Despite lacking statistical significance, 85% of patients reported subjective improvement of HFs with DR. After DR, the proportion of patients with endoxifen level <15 nM increased from 20% to 50%. HFS did not correlate with any other parameter. Conclusion: DR of tamoxifen from 20 mg to 10 mg daily resulted in halving of endoxifen levels and subjective improvement of HF. While half the dose-reduced patients were below a potential therapeutic level of endoxifen, other recent studies suggest that low endoxifen levels may not indicate reduced effectiveness of tamoxifen. Highlights: Halving tamoxifen dose halves endoxifen levels and subjectively improves hot flashes.